Sporadic Cryptosporidium infection in Nigerian children: risk factors with species identiﬁcation - TANNER, C. J.; MOLLOY, S. F.; KIRWAN, P.; ASAOLU, S. O.; SMITH, H. V. (Cambridge University Press, 2023)
Cambridge University Press,page NO:946–954